Pengaruh Tingkat Pendidikan, Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Pelayanan Teknik (Yantek) di ULP Singaraja - I Putu Agus Adnyana; I Kadek Romita Kusuma Jaya (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2022)
This study aims to determine the effect of education level, work motivation, and work discipline on the performance of Yantek employees at ULP Singaraja. In this study, three independent variables are education level, work motivation, and discipline, and use one variable, namely employee performance. The number of samples studied were 30 people using linear multiple research analysis. The results of this study are (1) Simultaneously the level of education, work motivation and work discipline have a positive and significant effect on the performance of Yantek employees at ULP Singaraja. (2) Partially the level of education does not have a significant effect on the performance of Yantek employees at ULP Singaraja. (3) Partially, work motivation has a positive and significant effect on the performance of Yantek employees at ULP Singaraja. (4) Partially, work discipline has a significant positive effect on the performance of Yantek employees at ULP Singaraja.